Mpu Kuturan dalam Teks Tutur - Ardiyasa, I Nyoman Suka (Humanis, 2023)
Manuscripts that mention Mpu Kuturan are found in various genres, such as speech texts, babad, usadha, kalpasastra, and inscription texts. The purpose of writing this scientific article is to explain in depth about the character Mpu Kuturan contained in the text Tutur of the Gedong Kirtya Singaraja collection. The analysis was carried out using a qualitative text method approach, also known as text interpretation research. The results of the research conducted obtained information that Mpu Kuturan, as a religious figure, had revitalized the Besakih temple and also taught the teachings of the Purana Tatwa, the Dewa Tatwa, the Widhisastra, Kusumadewa, Padma Bhuwana Prakempa, and Tingkahin Angwangun Kahyangan. Meanwhile, the ideology of Mpu Kuturan as an architect was found in Mpu Kuturan's thoughts on managing and perfecting the Besakih area, designing the establishment of Depangih méru, and managing palemahan with the concept of catur loka pala.